2013
DOI: 10.1302/0301-620x.95b3.29885
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of arthrodesis of the hindfoot as a salvage procedure for complex ankle pathology using the Ilizarov technique

Abstract: Achieving arthrodesis of the ankle can be difficult in the presence of infection, deformity, poor soft tissues and bone loss. We present a series of 48 patients with complex ankle pathology, treated with the Ilizarov technique. Infection was present in 30 patients and 30 had significant deformity before surgery. Outcome was assessed clinically and with patient-reported outcome measures (Modified American Orthopaedic Foot and Ankle Society (MAOFAS) scale and the Short-Form (SF-36)). Arthrodesis was achieved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 53 publications
2
23
0
Order By: Relevance
“…Our study is in line with the existing literature (i.e., Rochmann et al) reporting worse results than studies analyzing patients with tibiotalar arthrodesis [5,6,9,10,12]. Kugan et al also described a higher failure rate after loss of the talus in his study [13]. The calculated modified AOFAS score (max 86 points) was 53 points on average (min 25; max 68) in seven patients in this study, which is below the reported score of 65 points (eleven patients) in the study by Rochmann et al [12].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study is in line with the existing literature (i.e., Rochmann et al) reporting worse results than studies analyzing patients with tibiotalar arthrodesis [5,6,9,10,12]. Kugan et al also described a higher failure rate after loss of the talus in his study [13]. The calculated modified AOFAS score (max 86 points) was 53 points on average (min 25; max 68) in seven patients in this study, which is below the reported score of 65 points (eleven patients) in the study by Rochmann et al [12].…”
Section: Discussionsupporting
confidence: 92%
“…Since the introduction of compression arthrodesis by Charney in 1951, several different surgical procedures have been described as treatment options for ankle destruction of various etiologies [1]. Today, external Ilizarov arthrodesis represents an established and effective procedure in compromised hosts with acute or chronic infections, soft tissue defects, axial malpositions (varus/valgus) and comorbidities (diabetes mellitus, polyneuropathy, peripheral vascular disease, and alcohol abuse) [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Some authors even consider the Ilizarov method to be the "gold standard" in these difficult situations [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies report a statistically significant difference between the preoperative and postoperative AOFAS Scores by the use of Ilizarov fixator. [12][13][14] The average postoperative shortening was found to be 2.62cm in present study. Simultaneously proceeded with tibial lengthening along with ankle arthrodesis.…”
Section: Discussionsupporting
confidence: 58%
“…Kugan et al . 28 achieved an 83% fusion rate with satisfying functional improvement and no recurrence of previous deep infection in 48 patients with multiple comorbidities using the Ilizarov technique alone. Despite a few expected complications, most of which can be cured with early detection, IEF serves as a reasonable limb salvage alternative to amputation in this subset of patients 29 .…”
Section: Discussionmentioning
confidence: 96%